(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Absorption, emission and molecular docking characteristics of the naproxen drug with (DNA, RNA, BSA, Dendrimer) biomolecules and silver nanoparticles were analysed. With the addition of NP, the absorption and emission maxima of the biomolecules completely disappeared, and no significant spectral shift was noticed in the NP drug. When biomolecule concentrations increased, the absorption and emission intensities of the drug were gradually changed. The negative free energy values indicate the spontaneity of the binding between the drugs and biomolecules. van der Waals force and hydrogen bonding play major roles in the sensing of the drugs and biomolecules. Due to Ag nanoparticles interaction with NP/biomolecules, a blue or red shift was noticed in the absorption and emission spectra. Molecular docking results indicated that the biomolecules interacted with the O and H groups of the NP drug. The sensing behaviour of NP with DNA is higher than other biomolecules. NP drug demonstrates promising anticancer activity through interactions with both the 1r51 and 2oh4 EGFR protein targets.